Managing the Digital Competency of Educators and Students in the Age of Educational Transformation - Desmanto Zai; M. Giatman; Ambiyar; Dedy Irfan (Postgraduate, University of Mataram, 2025)
The education system is required to adapt to accommodate these developments and optimize students' digital competencies. Therefore, strengthening digital competencies is an urgent need in education to produce graduates who are ready to face global challenges.This study aims to analyze the relationship between students' digital competence and digital competence management towards digital education transformation at the Nias Regional Government Private Vocational School. The issues raised in this study are the low digital skills of students and the suboptimal management of digital competence by schools in supporting technology-based learning. This study uses a quantitative approach with a correlational method. The data collection technique was carried out by distributing questionnaires to grade XI students of the Nias Regional Government Private Vocational School, with a sample of 156 respondents taken using proportional random sampling technique. Data analysis was carried out using simple and multiple linear regression. The results of the study indicate a positive and significant relationship between students' digital competence towards digital education transformation, as well as between digital competence management towards digital education transformation. Simultaneously, these two variables contribute significantly to the acceleration of digital-based education transformation in the vocational school environment.